Acute Toxicity by Water Containing Hexavalent or Trivalent Chromium in Native Brazilian Fish, Piaractus mesopotamicus: Anatomopathological Alterations and Mortality - Castro, Marcello Pardi [UNESP]; Moraes, Flavio Ruas de [UNESP]; Fujimoto, Rodrigo Yudi; Cruz, Claudinei da; Andrade Belo, Marco Antonio de; Engracia de Moraes, Julieta Rodini [UNESP] (Springer, 2014)
This study evaluated the toxicity of hexavalent and trivalent compounds of chromium to the pacu, Piaractus mesopotamicus, in acute exposures of 96 h through mortality and histopathological responses. Hexavalent potassium dichromate was more toxic than trivalent compounds of chromium chloride, chromium oxide and chromium carbochelate. Sufficient mortalities occurred only with potassium dichromate to yield an LC50 value at 124.2 mg L-1. Hexavalent chromium caused reversible and irreversible lesions, which may affect organ functionality. Histopathological evaluation showed that trivalent chromium caused lesions of lower severity. Pacu subjected to different concentrations of chromium carbochelate showed no histopathological changes in the kidneys, liver, skin and gills, being similar to those of the control fish. Among the three sources of Cr3+, only chromium chloride at 200 mg L-1 resulted in mortality, which reached 100 % within the first 18 h. These findings confirm that trivalent chromium, when administered within recommended levels, may be used safely in aquaculture.
Keywords: Chromium; Toxicity; Piaractus mesopotamicus; Histopathology